CONSTITUTIONAL DESIGN OF LEGAL PROTECTION FOR JOURNALISTS FROM A HUMAN RIGHTS PERSPECTIVE - Brian Hafiz; Arif Hidayat (Universitas Negeri Semarang, 2026)
This research aims to analyze the constitutional design of legal protection for journalists in Indonesia from a Human Rights (HAM) perspective. The primary issue addressed is the significant gap between strong constitutional guarantees and the reality on the ground, which reveals high rates of violence and criminalization against journalists. Using a normative legal research method with a statute approach, the results indicate that although Article 28E and 28F of the 1945 Constitution and the ratification of the ICCPR provide a solid normative foundation, current protections remain declarative and lack operational efficacy. This shortfall is caused by regulatory disharmony, where the Press Law is frequently superseded by